Memule: Ritual Peringatan Arwah dalam Tradisi Jawa - Probosini, Agustina (Institut Seni Indonesia Yogyakarta, 2010)
Memule: After Death Commemoration Ritual Javanese Tradition. Javanese people believe in life after death. The belief is embodied in the form of traditional rituals and ceremonies that constitute Javanese cultural heritage. The sacred ceremony held to commemorate those who died is called memule and is carried out on days 3, 7, 40, 100, mendhaki (year - 1, 2) and day-to-1000 after someone passed away. Besides dominated by prayer, this ritual is sometimes added with an activity called macapat. It has been done by Javanese community since the prehistoric times. Until now it comprises the sacred aspects and magical aspects. The objective of the ritual is to express gratitude, to honor ancestors, and to seek safety for the spirits of the deceased and also the family left behind. Memule is believed to have a magic power that can lead to relationships. The relationship in question here is between human beings who are still alive in the mortal world with their ancestors' spirits who are also believed to be still alive in the afterlife. Incense (dupa) or perfumed powder used as incense (ratus), the photos of the deceased, and the incense derivedfrom gum benzoin (kemenyan) and offerings (sesaji) are examples of the magic contagious. Thus it can be said that memule ritual is a ritual done by the living to deeply honor the people who have passed away in the Javanese community. Keywords: Javanese community, death, soul, prayer.